2009
DOI: 10.1016/j.ajhg.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Human Brain Transcript Expression in Alzheimer Disease

Abstract: We recently surveyed the relationship between the human brain transcriptome and genome in a series of neuropathologically normal postmortem samples. We have now analyzed additional samples with a confirmed pathologic diagnosis of late-onset Alzheimer disease (LOAD; final n = 188 controls, 176 cases). Nine percent of the cortical transcripts that we analyzed had expression profiles correlated with their genotypes in the combined cohort, and approximately 5% of transcripts had SNP-transcript relationships that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
309
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(320 citation statements)
references
References 46 publications
8
309
2
1
Order By: Relevance
“…the transcriptional response associated with its onset and progression (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). These studies have revealed that this transcriptional response involves genes corresponding to proteins that can cause the disease and those associated with the cellular processes engaged in combating it (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the transcriptional response associated with its onset and progression (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). These studies have revealed that this transcriptional response involves genes corresponding to proteins that can cause the disease and those associated with the cellular processes engaged in combating it (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that this transcriptional response involves genes corresponding to proteins that can cause the disease and those associated with the cellular processes engaged in combating it (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Complex diseases, including AD, show a continuum of clinical phenotypes, such as the levels of Aβ accumulation. Transcriptome analysis, therefore, is preferred, because it is highly concordant with the disease state and expected to provide an accurate molecular view of a complex disease (25). Additionally, although quantitative trait loci analysis and a genome-wide association study identify genetic markers, they do not point to specific genes, whereas transcriptomics does (17).…”
Section: Discussionmentioning
confidence: 99%
“…We selected an AD gene expression data set from Gene Expression Omnibus (GEO, GSE15222). 24 This data set included 24 350 probes, 363 samples, 187 controls and 176 cases. First, we performed pretreatments, including using the mean value of gene expression when multiple probes corresponded to one gene and removing missing data lines and outliers.…”
Section: Materials and Methods Datamentioning
confidence: 99%